Measurement of drug concentration and bacterial contamination after diluting morphine for intrathecal administration: an experimental study - Aart Jan W. Teunissen; Mark V. Koning; Elisabeth J. Ruijgrok; Willem J. Liefers; Bart de Bruijn; Seppe A. Koopman (BMC Anesthesiology, 2020)
Abstract Background Low concentrations of morphine are required for safe dosing for intrathecal injections. Sometimes, manual dilution of morphine is performed to achieve these low concentrations, but risks dilution errors and bacterial contamination. The primary goal was to compare the concentrations of morphine and bupivacaine between four groups of syringes. The secondary goal was to investigate the difference in contamination rate between these groups. Methods Twenty-five experienced anesthesia providers were asked to prepare a mixture of bupivacaine 2.0 mg/ml and morphine 60 μg/ml using 3 different methods as clean and precise as possible. The fourth method used was the aspiration of ampoules prepared by the pharmacy. The concentrations of morphine and bupivacaine were measured by High-Pressure Liquid Chromatography (HPLC). The medication was cultured for bacterial contamination. Results Group 1 (median 60 μg/ml; 95% CI: 59–110 μg/ml) yielded 3 outliers above 180 μg/ml morphine concentration. Group 2 (76 μg/ml; 95% CI: 72–80 μg/ml) and 3 (69 μg/ml; 95% CI: 66–71 μg/ml) were consistently higher than the target concentration of 60 μg. The group “pharmacy” was precise and accurate (59 μg/ml; 95% CI: 59–59 μg/ml). Group 2 and “pharmacy” had one contaminated sample with a spore-forming aerobic gram-positive rod. Conclusion Manually diluted morphine is at risk for deviating concentrations, which could lead to increased side-effects. Medication produced by the hospital pharmacy was highly accurate. Furthermore, even when precautions are undertaken, contamination of the medication is a serious risk and appeared to be unrelated to the dilution process.